Teaching a dark chapter : history books and the Holocaust in Italy and the Germanys - Weiner, Daniela R. P., 1990- 1990- (Cornell University Press, 2024)
"The book studies how the Holocaust was taught in Italian, East German, and West German postwar history textbooks during the Cold War"--